Pisanie mikroraportów. Głos w sprawie obrazów i tekstów - Kalinowska , Katarzyna (Człowiek i Społeczeństwo, 2013)
The article presents the practical solutions applied during the process of writing micro reports from the observations and the interviews in the “Invisible city” research. Micro reports, which document a visuality and narratives built around images, are themselves a kind of visual compositions. The main purpose of this article is to show how the visualizations (visual memories, photographs, visual identifications of objects, places and people) are present in the different stages of the preparation of the texts. The article also raises issues of teamwork and its impact on the use of visual materials in the act of writing.